Code-switching in selected Malaysian celebrities’ instagram posts - Abdul Rahman, Sofia Hanis; Badaruddin, Zuraidar; Rashid Ali, Farrah Diebaa; Roslim, Norwati; Ismail, Marina (European Publisher, 2023)
With the advancement of technology nowadays, social media have become common platforms among Malaysian celebrities to communicate with their fans and to reach out to more people as a selfadvertisement to market themselves to be visible in the industry. Across these online platforms, distinctive speech behaviour has been observed among these celebrities in which they employ language alternation or code-switching. Numerous studies have primarily drawn emphasis on spoken c ommunication, resulting in a scarcity in written communication. Hence, this study aimed to investigate the use of code-switching among five Malaysian celebrities in their Instagram posts. An analysis was conducted to determine the types of code-switching employed in their online written communication. The frequency was also calculated in order to look for preferences across genders. The results indicated that Malaysian female celebrities employed all the different types of code-switching as compared to the male celebrities. The differences in using code-switching between female and male celebrities illustrated the gender preferences to accommodate the communicative strategies in their written communication.